The Art of Writing from the Border: Narrative Decentralisation and Pluricultural Identity Construction in Tomizza’s Franziska (1996) - Haaland, Torunn (Quaderni d'Italianistica, 2020)
This article examines one of Tomizza’s unjustifiably understudied texts within two primary contexts: one formed around the historical, political and social background of early 20th-Century Trieste, the other around the author’s recurrent concern with hybrid characters and geopolitical, cultural and linguistic borderlands. At the surface, these contexts are dramatised to revisit a political and ethnic conflict from the viewpoint of one of its most invisible victims. To uncover the novel’s more deep-running operations, however, this study takes a narratological approach and applies perspectives associated with imagology and linguistic hybridity as well as theories of border writing and border-crossing. Whereas the narrative fusion of historical reconstruction, self-reflexive commentaries, epistolary testimonies and mythical fictionalisations creates a discourse of literary fragmentation and deterritorialisation, the protagonist’s biographical background and socio-culturally embedded experiences are interlaced to represent a liminal character formed by dual perspectives, plurilingual enunciations and incompatible loyalties. Franziska exists between history and myth and as she increasingly acquires different cultural codes, she also comes to linger, irreconcilably, between different and conflicting cultural civilisations. Just as the multidimensional text questions norms of literary unity, so does this fluid character expose stereotypical conceptions of ethnic identities. As an amalgamated device, the self-referential narrator and the border crosser he constructs expose not only ideals of linguistic and cultural purity but also totalitarian conceptions of geographical and cultural borders. Ultimately, this experimental literary operation implicates the reader in a democratic literacy of multiple perspectives that questions normative notions of identities, belonging, culture and nationhood.